2017
DOI: 10.13164/re.2017.0552
|View full text |Cite
|
Sign up to set email alerts
|

Blind Audio Watermarking in Transform Domain Based on Singular Value Decomposition and Exponential-Log Operations

Abstract: Abstract. Digital watermarking has drawn extensive attention for copyright protection of multimedia data. This paper introduces a blind audio watermarking scheme in discrete cosine transform (DCT) domain based on singular value decomposition (SVD), exponential operation (EO), and logarithm operation (LO). In our proposed scheme, initially the original audio is segmented into non-overlapping frames and DCT is applied to each frame. Low frequency DCT coefficients are divided into sub-bands and power of each sub … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…Vivekananda [33] utilized DWT and SVD to propose an adaptive audio watermarking by applying a quantization index modulation (QIM) process on the SVD values in the DWT domain. Bhat [34] presented a SVD-DWT blind watermarking algorithm to embed watermark into the audio signals in which the quantization steps were determined by the statistical properties of the involved DWT coefficients. Lei [35] attempted to embed the watermark into the high frequency-band of the SVD-DCT block.…”
Section: Related Workmentioning
confidence: 99%
“…Vivekananda [33] utilized DWT and SVD to propose an adaptive audio watermarking by applying a quantization index modulation (QIM) process on the SVD values in the DWT domain. Bhat [34] presented a SVD-DWT blind watermarking algorithm to embed watermark into the audio signals in which the quantization steps were determined by the statistical properties of the involved DWT coefficients. Lei [35] attempted to embed the watermark into the high frequency-band of the SVD-DCT block.…”
Section: Related Workmentioning
confidence: 99%
“…However, this scheme shows less robustness against some of the common attacks. Dhar et al [7] proposed a DCT-based algorithm using singular value decomposition (SVD) and exponential-log operations (ELO) where the watermark is embedded to the highest power of DCT coefficients, but robustness results against some common attacks were not reported. Karnjana et al [8] introduced a method based on singular spectrum analysis (SSA) and psychoacoustic model (PM), but it shows quite low robustness against some common attacks.…”
Section: Related Researchmentioning
confidence: 99%
“…Simulation results demonstrated that our proposed method is highly robust against numerous attacks. The BER of the proposed method varies from 0 to 6.54, whereas the BER of the recent methods [4][5][6][7][8][9][10][11][12] vary from 0 to 17.76. The PSNR of the proposed method varies from 43.81 to 47.75, whereas PSNR of the recent methods vary from 19.39 to 44.81.…”
Section: Related Researchmentioning
confidence: 99%
See 2 more Smart Citations